Development of nanostructured green divalent manganese‐coordinated polyurea. Issue 41 (8th August 2022) - Laxmi,; Shahzaib, Adnan; Alam, Manawwer; Ghosal, Anujit; Zafar, Fahmina; Nishat, Nahid
Abstract: The work presented here reports the greener synthesis of polyurea (GPUa) via in‐situ solvent‐free precipitation polymerization of toluene diisocyanate (TDI) (used as monomer) and water. The divalent manganese [Mn(II)] ions were incorporated into GPUa to form Mn(II)‐GPUa to enhance its applicability. The structure of GPUa and Mn(II)‐GPUa was validated by Fourier‐transform infrared and proton nuclear magnetic resonance spectral techniques. The morphology along with the elemental analysis of GPUa and Mn(II)‐GPUa was assessed by X‐ray diffraction analysis and field emission scanning electron microscopy along with energy‐dispersive X‐ray spectroscopy. Thermal degradation behavior and stability of GPUa and Mn(II)‐GPUa were investigated by thermo‐gravimetric, differential thermal, differential scanning calorimetry, and integral procedure decomposition temperature analysis. Furthermore, the batch adsorption method was used to examine the adsorption behavior of Mn(II)‐GPUa. The study's results indicated that Mn(II)‐GPUa might be used as an eco‐friendly, thermally stable material and adsorbent, making it suitable as an effective dye adsorbent for wastewater treatment. The current work is aligned with Green chemistry principles (Principles 1, 2, 3, 4, 5, 6, 8, and 12). Abstract :